Viscous effects on squat. (August 2022) - Chillcce, Guillermo; el Moctar, Ould
Abstract: Potential theory was used to predict trim and sinkage of ships in shallow water for moderate water depths. However, for very shallow water depths leading to small under keel clearances, viscosity may have significant effects. Our paper presents a systematic numerical study on these effects. Numerical computations were carried out for the Duisburg Test Case containership in different water depths. The numerical predictions relied on inviscid, laminar, and turbulent flow assumptions. All calculations were performed on the same grid and with the same time step to ensure that discretization errors did not influence the results. Results showed that viscosity affected a ship's trim and that these viscous effects became more prevalent with decreasing under keel clearance. Highlights: Systematic study of molecular and turbulence viscosity effects on trim and sinkage of ships under moderate and extreme shallow water conditions. Potential, laminar and turbulent flow were computed under the same conditions. Systematic space and time discretization study were performed to ensure the quality of the computations.